1977
DOI: 10.1073/pnas.74.2.398
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of oxyhemoglobin.

Abstract: ABSTRACr When the magnetic susceptibility of frozen aqueous solutions of human oxyhemoglobin was measured in the range between 25 and 250 K, it showed a temperatur ependent behavior typical of a thermal equilibrium between a ground singlet state and an excited triplet state for two electrons per heme, the energy separation being 12JI = 146 cm-1. By contrast, within the same temperature range, carboxyhemoglobin was found to be diamagnetic, as already reported.Since the first magnetic studies by Pauling and Cory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…Fully liganded human HbCO and HbO2 samples were frozen, by immersion in liquid nitrogen, and inserted in the precooled sample chamber of the susceptometer, and their susceptibility was measured at 190 K. We do not detect any difference between the oxy and carbonmonoxy samples, in contrast to the results of ref. 1. Taken all together the present data do not allow any low-lying triplet state with an energy less than 1100 cm-' above the singlet ground state.…”
mentioning
confidence: 57%
“…Fully liganded human HbCO and HbO2 samples were frozen, by immersion in liquid nitrogen, and inserted in the precooled sample chamber of the susceptometer, and their susceptibility was measured at 190 K. We do not detect any difference between the oxy and carbonmonoxy samples, in contrast to the results of ref. 1. Taken all together the present data do not allow any low-lying triplet state with an energy less than 1100 cm-' above the singlet ground state.…”
mentioning
confidence: 57%
“…These values, being close to those of free superoxide ions (1100-1150 cm-'), have been taken as evidence of a substantial transfer of electron density from the iron (or cobalt) to the coordinated oxygen. The charge-transfer formulation of Fe(IJI)-02-or Co (III)-02 has, in fact, been proposed by many investigators (2,5,7,(11)(12)(13)(14), although there is not necessarily a transfer ofan electron from Fe (or Co) to 02 upon binding (4,15,16). The picture of single v(0-0) vibration is complicated by the discovery of an additional infrared band at 1156 cm-' in oxyHbA (17) after Collman et al (13) stretch at =570 cm-1 (originally reported at 567 cm'-) observed by Brunner (18), using resonance Raman spectroscopy.…”
Section: P(o-o) and V(fe-o) Stretching Vibrations The V(o-o)mentioning
confidence: 99%
“…Oxyhemoglobin, HbO,, another low-spin ferrous derivative, was reported some time ago to be distinctly paramagnetic at room temperature [3,4] . The fact that P,-inositol reduces the paramagnetism of carp HbCO seemed to conflict with earlier observations on the relationship between the quaternary state of the hemoglobin molecule and the spinstate equilibria of ferric derivatives of carp hemoglobin [5,6].…”
mentioning
confidence: 99%